Scattering of ultrasonic wave on a model of the artery - J. Wójcik; T. Powałowski; R. Tymkiewicz; A. Lamers; Z. Trawiński (Archives of Acoustics)
The study was aimed at elaboration of a mathematical model to describe the process of acoustic wave propagation in an inhomogeneous and absorbing medium, whereas the wave is generated by an ultrasonic probe. The modelling process covered the phenomenon of ultrasonic wave backscattering on an elastic pipe with dimensions similar to the artery section. Later on, the numerical codes were determined in order to calculate the fields of ultrasonic waves, as well as backscattered fields for various boundary conditions. Numerical calculations make it possible to define the waveforms for electric signals that are produced when ultrasonic waves, being reflected and backscattered by an artery model, are then received by the ultrasonic probe. It is the signal which pretty well corresponds with the actual RF signal that is obtained during measurements at the output of an ultrasonic apparatus.